2020
DOI: 10.1016/j.apsb.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of 5-cyano-6-phenylpyrimidin derivatives containing an 1,2,3-triazole moiety as potent FAD-based LSD1 inhibitors

Abstract: Histone lysine specific demethylase 1 (LSD1) has become a potential therapeutic target for the treatment of cancer. Discovery and develop novel and potent LSD1 inhibitors is a challenge, although several of them have already entered into clinical trials. Herein, for the first time, we reported the discovery of a series of 5-cyano-6-phenylpyrimidine derivatives as LSD1 inhibitors using flavin adenine dinucleotide (FAD) similarity-based designing strategy, of which compound 14q was finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…In 2020, our group reported a series of 5-cyano-6phenyl pyrimidine analogues containing the 1,2,3-triazole moiety to be FAD competitive LSD1 inhibitors (Figure 5B). 57 SARs studies identified compound 32 as the most potent candidate (IC 50 = 183 nM). Compound 32 was shown to inhibit LSD1 reversibly and time-dependently.…”
Section: Reversible Lsd1 Inhibitorsmentioning
confidence: 99%
“…In 2020, our group reported a series of 5-cyano-6phenyl pyrimidine analogues containing the 1,2,3-triazole moiety to be FAD competitive LSD1 inhibitors (Figure 5B). 57 SARs studies identified compound 32 as the most potent candidate (IC 50 = 183 nM). Compound 32 was shown to inhibit LSD1 reversibly and time-dependently.…”
Section: Reversible Lsd1 Inhibitorsmentioning
confidence: 99%
“…In comparison with irreversible LSD1 inhibitors, noncovalent reversible LSD1 inhibitors present potential advantages in phenotype and safety, and they are grouped into two categories: non-natural ones and natural products. In recent years, many research groups, including us, have designed and synthesized numerous noncovalent reversible LSD1 inhibitors with reduced toxicity, potent preclinical antileukemic effects, and sub-micromolar potencies, including dithiocarbamates, aminothiazole triazoles, pyrimidines, and triazole-fused pyridines. For instance, in 2019, our group identified of a series of triazole-fused pyrimidine derivatives as highly potent LSD1 inhibitors, of which the most potent compound (IC 50 = 49 nM) inhibited LSD1 reversibly and was highly selective to LSD1 over MAO-A and -B.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…The Lamarckian genetic algorithm was used for the conformational search of the inhibitor within the docking box size. During docking process, 100 independent runs were performed and the resulting poses were clustered using a root-mean-square deviation (RMSD) cutoff of 1 Å ( Ma et al, 2020 ; Wu et al, 2020 ). The docking pose with the lowest energy in the largest cluster was visually analyzed and then selected for the following MD simulations.…”
Section: Methodsmentioning
confidence: 99%